Respostas

2013-11-24T13:48:17-02:00
x=2           2y-2x=4
               2y-2*2=4
               2y-4=4
                2y=4+4
                 2y=8 
                  y=4                 (2,4)

x=2           2y-2x=4
                2y-2*3=4
                2y-6=4
                2y=4+6
               2y=10
                 y=5       (3,5)

x=2           2y-2x=4
                2y-2*4=4
                2y-8=4
               2y=4+8
               2y=12
               2y=6    (4,6)


obrigada pela força Andre valeu
:)